Teknologi WI-FI Menggunakan Topologi Star - Syuja Rifka Khairyansyah; Della Saskia Amalia; Subhan Aditya; Ardian Sah; Didik Aribowo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research uses Cisco Packet Tracer as a simulation tool for implementing WI-FI technology in a star topology. WI-FI technology is a wireless communication technology that allows electronic devices to connect wirelessly to a local area network (LAN). Star topology is one of the most commonly used network topologies, especially in wide local area networks (WLAN). This research uses Cisco Packet Tracer to model and simulate a star topology in WI-FI. This framework utilizes powerful simulation tools to facilitate network management and monitoring. Star topology can improve network performance because each device has a direct communication path to the access point. This research provides information about the basic concepts of WI-FI technology, introduces star topology and explains its implementation using Cisco Packet Tracer.